Formal peace and informal war : security and development in the congo - Marriage, Zoë (Routledge explorations in development studies ;, 2013)
Northern interventions into African countries at war are dominated by security concerns, bolstered by claims of shared returns and reinforcing processes of development and security. As global security and human security became prominent in development policy, Congo was wracked by violent rule, pillage, internal fighting, and invasion. In 2002, the Global and All-Inclusive Peace was promoted by northern donors, placing a formal peace on the mass of informalised wars. Formal Peace and Informal War: Security and Development in Congo examines how the security interests of the Congo.